An integrative expression vector for Actinosynnema pretiosum - Song Ruth (BMC Biotechnology, 2007)
Abstract Background The Actinomycete Actinosynnema pretiosum ssp. auranticum has commercial importance due to its production of ansamitocin P-3 (AP-3), a potent antitumor agent. One way to increase AP-3 production would be to constitutively express selected genes so as to relieve bottlenecks in the biosynthetic pathway; however, an integrative expression vector for A. pretiosum is lacking. The aim of this study was to construct a vector for heterologous gene expression in A. pretiosum. Results A series of integrative expression vectors have been made with the following features: the IS117 transposase from Streptomyces coelicolor, the constitutive ermE* promoter from Saccharopolyspora erythraea, different ribosome-binding site (RBS) sequences and xylE as a translational reporter. Positive E. coli clones and A. pretiosum transconjugants were assayed by catechol. pAP42, containing an E. coli consensus RBS, and pAP43, containing an asm19 RBS, gave strong and moderate gene expression, respectively. In addition, an operon construct capable of multi-gene expression was created. Plasmid integration sites in transconjugants were investigated and four different sites were observed. Although the most common integration site was within a putative ORF with sequence similarity to NADH-flavin reductase, AP-3 levels and cell growth of transconjugants were unaffected. Conclusion A set of integrative vectors for constitutive gene expression in A. pretiosum has been constructed. Gene translation is easily determined by colorimetric assay on an agar plate. The vectors are suitable for studies relating to AP-3 biosynthesis as they do not affect AP-3 production.